Conceptual Metaphors of Nature in Sasak Language: A Cognitive Semantic Analysis of Indigenous Environmental Knowledge - Syamsurrijal Syamsurrijal; Erwin Suhendra; Wahyu Kamil Syarifaturrahman; Muhlisin Muhlisin (Humanitatis : Journal of Language and Literature, 2026)
Indigenous languages have been shown to play a crucial role in preserving ecological knowledge, cultural memory, and community identity. However, the semantic dimensions through which environmental knowledge is encoded in many indigenous languages remain underexplored, particularly in underrepresented Austronesian languages such as Sasak. The specific aims of this study are threefold: first, to identify the semantic categories of environmental concepts; second, to examine the conceptual metaphors underlying indigenous ecological knowledge; and third, to explain how these semantic structures reflect Sasak cultural cognition and identity. The present research employed a qualitative descriptive method within an interpretive paradigm. Data were collected from 25 native Sasak speakers selected through purposive sampling from East, Central, and West Lombok. The data comprised environmental vocabulary, proverbs, folklore narratives, oral traditions, and customary expressions gathered through semi-structured interviews, participant observation, and documentary analysis. The findings reveal that environmental knowledge in the Sasak language is organised into five interconnected semantic domains: water resources, landscapes, flora, fauna, and environmental processes. Of these domains, the water-related domain is particularly prominent, reflecting the ecological and cultural significance of water in Sasak society. The study further identifies several conceptual metaphors in which environmental phenomena function as source domains for abstract cultural meanings, including social harmony as ecological balance, causes as natural forces, and human identity as a rooted tree. These metaphorical structures illustrate how environmental observations are transformed into cognitive models for interpreting social relationships, moral values, and collective responsibilities. Furthermore, the analysis of environmental concepts embedded in proverbs, folklore, and cultural narratives reveals shared conceptualisations that emphasise harmony, interdependence, environmental stewardship, and communal identity.